Characteristics of Arable Land Valuation in Hungary - Tamás Nándor Tógyer (Theory, Methodology, Practice, 2012)
Since the transition, the different asset valuation methods have gained an increasing importance in agriculture. Land assessment has a high priority in agriculture, since it is the basis and an indispensable resource of the branch. Hungarian land prices are low, which is mainly due to two factors; the lack of land sales, and low farm incomes. Further issues to be addressed are what the old gold-crown system should be replaced with, and also if economic and ecological land evaluations should go together. In this context, it is also necessary to decide whether a uniform land valuation system has to be introduced, or whether the choice of a method suiting the purpose of valuation will always be the most effective.